SELF EFFICACY AS A DETERMINATION OF STUDENTS ENTREPRENEURIAL INTENTION (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
The problem in this research is the increase in unemployment among college graduates where college graduates should essentially be able to produce graduates who must have entrepreneurial skills so as to reduce the ongoing unemployment rate. This study aims at determining and analyzing the effect of self-efficacy on entrepreneurial interest of students at Economics Education Study Program, STKIP PGRI, West Sumatera. The method used in this study is survey with a descriptive quantitative approach. Data collection techniques in this study used questionnaire using a Likert scale of 1-5. The object of this research is the students of the Economics Education Study Program at STKIP PGRI West Sumatera by determining the sample using the Slovin formula. The data analysis used in this study is a simple linear regression analysis which aims to determine the test of the effect of this research variable in the form of self-efficacy on student interest in entrepreneurship. The results of the research that have been conducted reveal that self-efficacy of students has a significant effect on the interest in entrepreneurship with a confidence level of 5% and the results of the research prove that the significant value is 0,000 which indicates that the value is less than 0.05. Based on these results, efforts need to be made to increase entrepreneurial intention of students of Economics Education Study Program at STKIP PGRI West Sumatera, one of which is by providing facilities and infrastructure that support entrepreneurial activities. Keyword: self-efficacy, entrepreneurial interest